Penerapan Slow Deep Breathing Terhadap Penurunan Tingkat Nyeri Pada Pasien Hipertensi Di IGD Rs Ibnu Sina YW.UMI Makassar - Widiya Satuwo; Sudarman Sudarman; Idelriani Idelriani; Rochfika Rochfika (Wal'afiat Hospital Journal, 2025)
Hypertension is a chronic condition characterized by increased blood pressure in the arteries, which can disrupt the supply of oxygen and nutrients to body tissues. One nursing intervention for pain management in hypertensive patients is the slow deep breathing (SDB) technique. This technique can reduce pain intensity, stabilize heart rate and blood pressure, alleviate muscle tension, and improve patient well-being. This study aims to evaluate the effectiveness of SDB in reducing pain levels among hypertensive patients in the Emergency Department of RS Ibnu Sina YW.UMI Makassar. The implementation of this nursing intervention showed significant results, with a reduction in patients' pain levels from moderate (NRS 6) to mild (NRS 4), leading to a decrease in headache complaints. These findings indicate that SDB is an effective and efficient method for alleviating pain in hypertensive patients, making it a practical and applicable non-pharmacological intervention in healthcare settings.